Zp4 is completely dispensable for fertility in female rats. Issue 6 (11th March 2021) - Zeng, Ming-Hua; Wang, Yan; Huang, Hua-Lin; Quan, Ru-Ping; Yang, Jun-Ting; Guo, Dan; Sun, Ying; Lv, Chao; Li, Tian-Ying; Wang, Le; Tan, Hang-Jin; Long, Pan-Pan; et al.
Abstract: Zona pellucida (ZP), which is composed of at most four extracellular glycoproteins (ZP1, ZP2, ZP3, and ZP4) in mammals, shelters the oocytes and is vital in female fertility. Several studies have identified the indispensable roles of ZP1–3 in maintaining normal female fertility. However, the understanding of ZP4 is still very poor because only one study on ZP4-associated infertility performed in rabbits has been reported up to date. Here we investigated the function of mammalian Zp4 by creating a knockout (KO) rat strain ( Zp4 −/− rat) using CRISPR–Cas9-mediated DNA-editing method. The influence of Zp4 KO on ZP morphology and some pivotal processes of reproduction, including oogenesis, ovulation, fertilization, and pup production, were studied using periodic acid–Schiff's staining, superovulation, in vitro fertilization, and natural mating. The ZP morphology in Zp4 −/− rats was normal, and none of these pivotal processes was affected. This study renewed the knowledge of mammalian Zp4 by suggesting that Zp4 was completely dispensable for female fertility. Abstract : Zp4 is completely dispensable for female fertility in rats.